(untitled) (Research, Society and Development, 2021)
This work analyzes the use of antimicrobials in a Neonatal Intensive Care Unit, based on the pharmacotherapeutic field. It’s a cross-sectional study carried out from June to December 2018. It was observed that 124 patients were admitted to the Neonatal Intensive Care Unit. 56 of those attended the research inclusion criteria. As for the characteristics of the studied population, 60.7% were male, the main diagnostic hypothesis of infection in neonates was early sepsis, corresponding to 55.3%. 23 (41%) of the studied patients had positive blood culture, and the main isolated bacterium was coagulase negative Staphylococcus. The frequency of antimicrobials prescribed per patient varied: 5 (9%) used only 1 antimicrobial, 28 (50%) used between 2 and 3 antimicrobials and 23 (41%) used more than 3 antimicrobials. The most prescribed antimicrobials were gentamicin, 33 (15.7%), ampicillin, 32 (15.2%), amikacin, 27 (12.8%) and Oxacillin, 23 (11%). Regarding the days of treatment, vancomycin and meropenem were the prescription drugs that last the longest, both with 56 days. The data presented showed that the profile of the studied neonatal ICU follows a worldwide trend, encouraging the need to develop health policies that prioritize the rational use of antimicrobials.